From Text to Action: AI-Driven Classification of Public Service Complaints in Karanganyar, Indonesia - Muhammad Zainudin Al Amin; Farel Imam Maulana; Riefandi Dwiki Surya Putra; Mohammad Nurul Huda (S1 Teknologi Informasi, Universitas Muhammadiyah Semarang, 2025)
Efficiently classifying public complaints is crucial for fostering transparent and responsive governance in the digital age. However, the sheer volume and textual nature of complaint data pose significant challenges for manual categorization, particularly within local government systems. This study seeks to develop an automatic classification model for public complaints by employing Logistic Regression and TF-IDF vectorization. The dataset, comprising complaints submitted to the Karanganyar Regency Government from January to June 2025, underwent preprocessing through standard natural language techniques and was converted into numerical features using TF-IDF. Logistic Regression was chosen for its simplicity, interpretability, and effectiveness with sparse text data. To address class imbalance, class weighting and stratified sampling were utilized. The model achieved an overall accuracy of 61%, surpassing the Naive Bayes baseline. Confusion matrix analysis demonstrated strong performance in dominant categories, although minority classes continued to present challenges. The results suggest that Logistic Regression offers a practical and explainable solution for early-stage complaint classification systems, especially in public sector contexts. This study lays the foundation for the future development of intelligent e-government platforms capable of real-time complaint handling.